Ecossistemas empreendedores: estudo de caso - Valente, Fernando (2019)
The promotion of conditions that stimulate the emergence of new companies, support their rapid growth and their innovative capacity has been deserving special attention from several public and private entities. This interest is based on the expectation of business and social regeneration and the economic growth of the regions where these new companies are created. The conditions for its formation and growth depend on a set of actors who often include universities, investors, incubators, public entities, among others. Academically speaking, this finding culminated in an emerging approach of the entrepreneurial ecosystem which focuses on understanding how contexts affect entrepreneurship. This article aims to understand the relationship between entrepreneurship and the entrepreneurial ecosystems, and how these phenomena attempt to explain the creation of new companies. The main objective of this article is to explain how different configurations of the ecosystem (Coimbra and Sines) produce results with its own specificities and characteristics.